The Role, Use and Activation of Strong and Weak Network Ties: A Qualitative Analysis* - Jack, Sarah L. (Journal of Management Studies, 2005)
abstract A characteristic of studies seeking to explain the structure and operation of networks is the use of Granovetter's strong and weak tie hypothesis. Whilst this hypothesis has become an established paradigm, questions and disagreements arise over its applicability at demonstrating the real use and value of each tie. This study extends the work of Granovetter. Using a qualitative ethnographic approach to explore in‐depth the networking activities of fourteen respondents, it aims to enhance understanding about the role of ties, how they are used and activated for business activity. Findings demonstrate that it is strong ties that are instrumental for business activity and used extensively to provide knowledge and information but also to maintain, extend and enhance business and personal reputations. Unless activities require their reactivation and manifestation, strong ties remain latent and dormant within the network. Strong ties also provide the mechanism to invoke ‘weak’ ties, represented by nodes operating in a wider social context.